2021
DOI: 10.1155/2021/4187398
|View full text |Cite
|
Sign up to set email alerts
|

CaMK II Inhibition Attenuates ROS Dependent Necroptosis in Acinar Cells and Protects against Acute Pancreatitis in Mice

Abstract: As a calcium-regulated protein, CaMK II is closely related to cell death, and it participates in the development of pathological processes such as reperfusion injury, myocardial infarction, and oligodendrocyte death. The function of CaMK II activation in acute pancreatitis (AP) remains unclear. In our study, we confirmed that the expression of p-CaMK II was increased significantly and consistently in injured pancreatic tissues after caerulein-induced AP. Then, we found that KN93, an inhibitor of CaMK II, could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Fresh pancreas samples were fixed in 4% paraformaldehyde, embedded in paraffin for hematoxylin and eosin staining (H&E) and examined by light microscopy (400×). Two investigators who were blinded to the experimental treatment scored the degree of tissue injury; the scoring standards were described previously [37].…”
Section: He Stainingmentioning
confidence: 99%
“…Fresh pancreas samples were fixed in 4% paraformaldehyde, embedded in paraffin for hematoxylin and eosin staining (H&E) and examined by light microscopy (400×). Two investigators who were blinded to the experimental treatment scored the degree of tissue injury; the scoring standards were described previously [37].…”
Section: He Stainingmentioning
confidence: 99%
“…Our results showed that consistent with the Ca 2+ chelation, the inhibition of MLKL decreased the cytosolic Ca 2+ overload, indicating that Ca 2+ influxes were partly dependent on MLKL in ZEA-treated gESCs. In addition, studies implicated that Ca 2+ influxes raised cellular ROS and mediated the mitochondrial damage, thus promoting cell necroptosis in cardiac IR injury, acute pancreatitis, and heart failure [ 20 , 39 , 40 ]. In the current study, we showed that cytosolic Ca 2+ chelation with BAPTA-AM markedly inhibited the overproduction of ROS and alleviated the mitochondrial damage in gESCs caused by ZEA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…CaMK II is a calcium-modulating protein that is upregulated in the pancreatic acinar cells of AP mice. It has been discovered that its inhibitor, KN93, protected against AP in mice by reducing oxidative stress products, reducing the expression levels of the RIPK3 and p-MLKL pathways and preventing necroptosis [ 103 ]. Some studies have evinced that inhibiting Hif-1α also alleviates AP by reducing the production of ROS and regulating the necroptosis signaling pathway [ 104 ].…”
Section: Pancreatitismentioning
confidence: 99%